A clinico-pathological study of minor salivary gland tumors: experience of our institute - Sharma, Sourabh; Kumar, Vikesh; Thakkar, Konark; Shandilya, Yugam Prasad (International Journal of Research in Medical Sciences, 2024)
Background: Minor salivary glands are found throughout the entire upper aerodigestive tract. Minor salivary gland neoplasms represent less than 25% of intraoral salivary neoplasms. There are no uniform guidelines at present for treatment for minor salivary gland tumors as these are rare entities. The objective of the study was to evaluate the clinicopathological profile of minor salivary gland tumors and to evaluate follow up of patients after treatment. Methods: The present study was a prospective observational study conducted on 11 patients of the Pacific Medical College and Hospital, Udaipur from 1 December 2020 to 31 December 2023 with complaints of intra-oral swelling with biopsy proven MSGT were included. Results: Out of 11 patients, 7 were female and 4 were male. Highest incidence was found in patients in the 4th-5th decade of life. For most patients, painless swelling was the primary presentation. The most common site for minor salivary cancer was the hard palate 55%. The most common histological types were adenocystic carcinoma. In 10 cases complete surgical excision with clear margins was the preferred mode of treatment. In 1 palliative therapy was required. Among 11 patients, 2 required radiotherapy. Conclusions: MSGT are rare, early diagnosed and resection with wide margins/neck dissections + SOS adjuvant therapy is key to treatment.